PEMBUATAN BENANG OPERASI DARI ECENG GONDOK - Sari Purnavita; Lucia Hermawati Rahayu; Sri Sutanti (Universitas PGRI Semarang, 2018)
Operating thread needs in Indonesia to increase, but until now to supply the needs of operating threads absorbed (can be integrated with the body) still depends on imported products that are expensive. To reduce Indonesia's dependence on biomaterials imports in the field of biomedicine, it can be done through the engineering of operating yarn production absorbed from Indonesia's natural resources. Poly Lactic Acid (PLA) is a polymer that is widely applied as a biomaterial in biomedical fields such as operating threads. In this research, absorbable suture was made from poly lactic acid poly polymer blend from water hyacinth with natural glucomannan polymer of iles-iles. The aim of the study was to study: 1) the effect of polymerization reaction time on PLA yields and 2) the effect of poly lactic acid-glucomannan composition on the mechanical properties of operating threads. Making PLA using the ring opening polymerization method and making yarn using the wet spinning method. The independent variables at the manufacturing stage of the PLA polymer are reaction time = 60, 90, 120, and 150 minutes, while for the variable at the stage of operation yarn making is the ratio between the PLA period: glucomannan = (1: 3); (1: 2); ( 1: 1); (2: 1); (3: 1). The results showed that: 1) reaction time had a very significant effect on yield PLA and 2) different composition of poly lactic acid - glucomannan gave different tensile strength and tensile elongation values. Keywords: water hyacinth, poly lactic acid, glucomannan, operating thread